Peran PKn dalam Membentuk Budaya Anti-Perundungan di Lingkungan Sekolah Dasar - Sari, Ratna Kartika; Gofur, Abdul (Academy of Social Science and Global Citizenship Journal, 2025)
Bullying in elementary school environments is a serious challenge in education that negatively impacts students' character development and psychological well-being. Civic Education (PKn) holds strategic potential in preventing bullying by instilling values of democracy, tolerance, empathy, and social responsibility. This study aims to examine the role of PKn in fostering an anti-bullying culture in elementary schools through a library research method. Data were collected from various academic literature and analyzed descriptively and qualitatively. The findings indicate that value-based PKn learning can raise students' moral awareness about the importance of living peacefully and respecting differences. Civic Education teachers play a significant role as role models in internalizing anti-bullying values through contextual learning strategies. Furthermore, the “Roots” program by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) and UNICEF, which involves students as agents of change, strengthens the synergy between character education and civic learning. Thus, PKn contributes greatly to creating a safe, inclusive, and bullying-free school environment.